Research in finance. Vol. 24 - Chen, Andrew H. (Emerald, 2008)
This volume contains contributions on a range of important issues in current research in finance and economics. Topics include the IPO underwriting spreads, the moral hazard problems in bank regulation as well as in the cost of deposit insurance, the loan yield spreads, and the aggregate bank performance at the state-level. The topics in global investments such as diversification benefits, overreaction and seasonality among international stock markets are also included in this volume. The contributions to this volume also address the appropriate asset allocation of hedge funds, the effects of partial hedging in incentive stocks and options, the relation between board size and firm performance, the impact of higher oil prices on stock market returns, and the futures hedging effectiveness with alternative settlement specifications in the contracts.This volume contains articles contributed by leading experts in finance and economics. It includes articles on the hot topics of oil-prices and hedge-funds.
Keywords: Finance -- Research.; Banks and banking.; elektronické knihy; electronic books